Roman agrarian policies and the Italian countryside 133–91 BC - Kim, YC (2016)
This thesis is an investigation into the economic background to the Social War (91–88 BC), a rebellion against the Roman Republic by Rome’s allies in Italy, and examines the allied reception of Roman agrarian schemes in the decades prior to the Social War, with particular attention to free small-scale farmers. It has been argued that the consequences of the Gracchan agrarian reforms contributed to the decision of the Italians to revolt in 91 BC. The history of the Gracchan period, however, suffers from limited documentary sources. Furthermore, as Romano-centric preconceptions underlay many modern studies in which the Social War was understood as a fight for the Roman citizenship, the Gracchan reforms and the post-Gracchan agrarian policies have not been fully explored from an allied perspective. After reviewing the demographic approach to the ‘second-century rural crisis’ which allergedly prompted the Gracchan reforms, the thesis attempts to understand the operations of the Gracchan reforms in the territories of the Latin and Italian states via an archaeological case-study of the Latin town of Luceria in northern Apulia, where large areas of the Roman land division and settlement system known as centuriation were identified near the town. The thesis moves on to the post-Gracchan era and investigates how the allied interest in Roman public land (ager publicus) was continuously threatened or neglected under the post-Gracchan agrarian legislation (121–111 BC), and argues that allied small-scale farmers in particular stood to lose a lot in this process. The thesis then endeavours to demonstrate how the political aspirations of the allies had evolved in tandem with Roman agrarian policies, from a request for passive protection from maltreatment by Romans in the 120s BC to the demand for an active share in power by 91 BC. The thesis discusses Saturninus’ agrarian schemes in 103 and 100 BC, whose implications have been neglected in the context both of Roman agrarian history and the Social War, and presents Livius Drusus’ scheme of extensive colonisation of Italy in 91 BC as a complete reversal of policy, contravening the post-Gracchan agrarian settlement which had confirmed the end of land distributions in Italy. The thesis concludes by arguing that the Roman agrarian policy on the redistribution of public land was the cause of the most consistent and systematic maltreatment of the theoretically autonomous allied states, in which the inequality between Romans and Italians was increasingly highlighted.